2010
DOI: 10.1111/j.1747-0765.2009.00428.x
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of microbial biomass nitrogen in relation to plant nitrogen uptake during the crop growth period in a dry tropical cropland in Tanzania

Abstract: Soil microbes are considered to be an important N pool in dry tropical croplands, which are nutrient poor. To evaluate the N contribution of soil microbes to plant growth in a dry tropical cropland, we conducted a maize cultivation experiment in Tanzania using different land management treatments (no input, plant residue application, fertilizer application, plant residue and fertilizer application, and non-cultivated plots). Over 104 experimental days, we periodically evaluated the microbial biomass N and C, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 37 publications
(86 reference statements)
3
22
3
Order By: Relevance
“…Meanwhile, it can be said that critical N deficiency did not occur after the application of maize residues either through incorporation or mulching. Sugihara et al (2010a) showed that microorganism behaved as a sink of N through the decomposition of incorporated crop residue without a severe N deficiency in Tanzanian maize cropland.…”
Section: Effects Of Application Methods Of Crop Residues On the Dynamimentioning
confidence: 99%
“…Meanwhile, it can be said that critical N deficiency did not occur after the application of maize residues either through incorporation or mulching. Sugihara et al (2010a) showed that microorganism behaved as a sink of N through the decomposition of incorporated crop residue without a severe N deficiency in Tanzanian maize cropland.…”
Section: Effects Of Application Methods Of Crop Residues On the Dynamimentioning
confidence: 99%
“…Increasing microbial N uptake rates under sludge treatment leads to the possibility of improving nitrogen use efficiency in both soils. These results indicated that organic amendments with high C content as shown in sludge (Table 1) may increase the N immobilization by soil microbes, resulting in a lower rate and longer period of N uptake by plants [28]. Positive correlations were found between N uptake and both of the microbial N uptake and P fix in both clay soil (R = 0.96 and R = 0.98, resp.)…”
Section: Effect Of Different Nitrogen Sources On Microbial Biomass Nimentioning
confidence: 81%
“…Nitrogen uptake in rice shoot was determined by multiplying the N concentration by shoot dry weight. The total amount of microbial N absorbed by rice plant was determined by N difference method at maximum tillering stage [8,[25][26][27][28]. Amount of microbial N was calculated from the difference between the extractable N from fresh soil and autoclaved soil samples under the same treatment as shown in the following equation.…”
Section: Rice Plant Analysesmentioning
confidence: 99%
“…Therefore, it is necessary to reduce the N leaching resulting from heavy rainfall at the early crop growth stage (Shahandeh et al. 2004; Sugihara et al. 2010b).…”
Section: Discussionmentioning
confidence: 99%
“…In this season, the amount of N taken up by the crops is quite important for crop growth in later stages as well as yield. Therefore, it is necessary to reduce the N leaching resulting from heavy rainfall at the early crop growth stage (Shahandeh et al 2004;Sugihara et al 2010b). Judging from the THs-W plot where the level of inorganic N remained relatively steady for the first 100 h, increased In-situ-MB after the rainfall treatment was considered to immobilize the mineralized N after rewetting of the dry soil, and after 110 h, decreasing In-situ-MB in the THs-W plot appeared to supply 0.2 g N m )2 .…”
Section: Relationship Between Nitrogen Dynamics and Microbial Dynamicmentioning
confidence: 99%